Dengue Fever, Expanded Dengue Syndrome and Dengue Shock Syndrome: Clinical Profile, Management and Outcome of Patients at a Tertiary Hospital, Dhaka, Bangladesh - rouf, Rozana; rabbani, Raihan; rabbani, Raihan; dewan, Pratik; uddin, Mirza Nazim; alam, Jahangir; hassan, Kazi Ali; bakar, Md Abu; amin, Md Robed; hossain, Anowar (Bangladesh Journal of Medicine, 2020)
Background: Dengue fever is endemic in Bangladesh. Its incidence has been increasing and spreadingfrom urban Dhaka to rural areas. In 2019, over 100,000 cases reported with deaths over 250.Clinical profiles varied from classical signs and symptoms to alarming severity and complications,such as, Expanded Dengue Syndrome (EDS), Dengue Shock Syndrome (DSS) along with coinfectionsand comorbidities. No detail study on EDS & DSS carried out yet over 2019 outbreak. This reporthighlights the features, management and the outcome of EDS & DSS cases of 2018-19 admitted in aspecialized tertiary private hospital in Dhaka, Bangladesh. Methods: This cross sectional observational study was performed at Square Hospital, Dhaka,exclusively over 62 adult dengue patients with complications who fulfilled the admission criteria inICU and HDU and managed as per national guidelines and diagnosed by positive NS1 Ag, DengueRT PCR , Anti-dengue IgM, hematological and biochemical tests. Results: Of 343 cases, 62 (18.1%) patients had complications; 17 (27.4%) admitted in ICU and 45(72.6%) patients in HDU. Among 62 patients, 25 patients had EDS (40.3%) and 17 had DSS (27.4%).Of the EDS patients, majority were 40-50 years old with male predominance. Of 62 patients, 42 hadatypical presentations (67.74%), 25 (40.3%) had EDS and 17 (27.4%) had DSS, 16 (25.8%) had coinfection,45 (72.58%) had co-morbidities. Most patients presented with gastrointestinal symptoms(80%). Twenty one cases (84%) of EDS survive; 4 (16%), died after developing rhabdomyolysis, multiorgandysfunction and acute renal failure. Conclusion: Early diagnosis of complicated cases by clinical features, lab predictors and early fluidtherapy are the key to successful management with positive outcome. Death could be averted byrecognizing the stage of plasma leakage indicated by raised CRP, reduced serum Albumin, andultrasonography for detecting ascites, pleural effusion, mucosal thickening and edema of gall bladderand appropriate replacement of fluid loss and maintenance of nutrition. Bangladesh J Medicine July 2020; 31(2) :58-63